Human Health and Nutritional Value of Walnut and Evaluation of its Sensory, Peroxidase and Acid (Medico Legal Update, 2020)
Sensory evolution of walnut fruit sere testes by groups of assessors some lecturer in my department whomthey have perfectly experience of this purpose. Acid value and Peroxidase value are tested to illustrate changein oiliness and changing in the taste, flavor, odor,texture and kernel color and to notice the differences amongtwo storage condition in two different temperature (4°C, 25°C), in zero time after 18months of storage visualproperties of kernel walnuts there were some properties evaluated in walnut (appearance of kernel, to assessits flavor, bitterness, astringency, texture, crispness and oiliness. Visual appearance of Kernel of walnutswas evaluated similarly by both groups of assessors. However, each group of assessors had quite differentperceptions for tasting internal traits of the kernels. In the present study useful data of sensory characteristicsof walnut fruits were obtained.